The Evaluation of Strength, Flexibility, and Functional Performance in the Adolescent Ballet Dancer During Intensive Dance Training. Issue 7 (13th February 2019) - Yin, Amy X.; Geminiani, Ellen; Quinn, Bridget; Owen, Michael; Kinney, Susan; McCrystal, Tara; Stracciolini, Andrea
Abstract: Background: Adolescent ballet dancers have a higher incidence of injury than adult professional dancers. It is unclear which factors, including biomechanical changes related to intense dance training and/or the growth process itself, contribute to increased injury risk in this population. Objective: To assess changes in strength, flexibility, and functional performance in adolescent ballet dancers during a summer intensive dance program. Design: Prospective cohort study. Setting: Performing arts school in a suburb of Massachusetts. Participants: A convenience sample of 58 male and female ballet dancers, 12 to 17 years old, was enrolled. One dancer did not have functional testing due to injury, but strength and range of motion results were included. Methods: Paired sample t ‐test was used to evaluate changes in (1) strength: lower abdominal muscle strength evaluated by the Kendall double leg lowering test; (2) flexibility: passive range of motion in hip extensibility, hip internal rotation, hip external rotation, hip turnout, and ankle dorsiflexion; and (3) functional athletic and dance assessment: the star excursion balance test (SEBT), vertical jump test, and dance technique performing demi‐plié and passé dance positions. Main Outcome Measurements: Change in strength, flexibility, and functional dance measurements pre‐ and postsummer intensive dance training. Results: Lower abdominal strength testing improved 11° on the Kendall test ( P  < .001); lower extremity passive flexibility was reduced in all tested ranges bilaterally. Dance technique, in performing demi‐plié and passé dance positions, improved. More dancers demonstrated correct knee alignment during demi‐plié ( P  < .001‐.002) and hip alignment during plié ( P  = .01‐.04). Dancers also had greater active hip turnout in first position passé of 2 to 3° ( P  = .02‐.05). No significant change was found in functional athletic performance as measured by the SEBT and vertical jump test. Conclusion: Adolescent dancers in this study cohort who participated in a summer intensive dance program improved lower abdominal muscle strength as well as functional dance technique in demonstrating correct alignment performing demi‐plié and passé dance positions despite a decrease in passive lower extremity range of motion. Further research is needed to clarify the role of these findings in training for young dancers in order to move forward injury prevention efforts. Level of Evidence: II